Sustainable development of Chinese family businesses: exploring the role of succession planning in maintaining organizational sustainability from the perspective of socioemotional wealth - Li, Zeyu; Mustapha, Mazlina; Sheikh Hassan, Ahmad Fahmi; Saidin, Saidatunur Fauzi (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Identifying the factors affecting organizational sustainability is a crucial topic in the field of social science and business research. Especially in family businesses, the most crucial issue is how to maintain corporate sustainability across generations. In this regard, succession planning plays a key role in maintaining the sustainable development of family businesses. From the perspective of socioemotional wealth, this study discusses the motivations and consequences of intrafamily succession by measuring the impact of the internal determining factors of succession planning on family business performance. Based on a sample of 281 Chinese family firms, this study uncovers the relationship between succession planning and organizational performance. The core findings of this study include succession planning is positively related to organizational performance in the matter of the successor’s training; succession planning has a positive effect on organizational performance in terms of the successor’s self-preparation; and succession planning is positively correlated with organizational performance in the aspect of the relationship between the successor and business. By illustrating that the formulation of succession planning is an essential pursuit for family businesses to preserve sustainability and socioemotional wealth, the results reveal ways to facilitate succession planning through internal factors in the family business. This study contributes to organizational sustainable development literature, family business sustainability studies, and succession management research by validating the positive relationship between succession planning and organizational performance, indicating that succession planning is a vital driving force for achieving organizational sustainability.